1985
DOI: 10.1116/1.572902
|View full text |Cite
|
Sign up to set email alerts
|

TiB2 and ZrB2 diffusion barriers in GaAs Ohmic contact technology

Abstract: The transition metal diboride compounds, ZrB 2 and TiB 2 , interposed between Ni/Ge/ Au Ohmic contact metallization on n-type GaAs wafers and an overlying thick Au contact layer, have been investigated to evaluate their effectiveness in stabilizing the Ohmic contact by limiting the indiffusion of Au. All of the metal layers were e-beam deposited except the ZrB 2 which was rf-diode sputtered. The barrier layer thicknesses were 50 and 100 nm for the TiB 2 and the ZrB 2 , respectively. Postdeposition alloying of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…[5,7] Combined with remarkable high temperature stability, these properties make ZrB 2 an attractive material for thin film based electronic devices that must withstand harsh, high temperature environments. [7,8] For several decades is has been known that agglomeration limits the morphological stability of metallic thin films at elevated temperatures, [9,10] where the dewetting process is driven by atomic 10 diffusion that minimizes the total surface and interfacial energy of the system. [11] Some success has been achieved in avoiding agglomeration in Pt films by using adhesion layers and combining Pt with nanostructured oxide phases.…”
Section: Introductionmentioning
confidence: 99%
“…[5,7] Combined with remarkable high temperature stability, these properties make ZrB 2 an attractive material for thin film based electronic devices that must withstand harsh, high temperature environments. [7,8] For several decades is has been known that agglomeration limits the morphological stability of metallic thin films at elevated temperatures, [9,10] where the dewetting process is driven by atomic 10 diffusion that minimizes the total surface and interfacial energy of the system. [11] Some success has been achieved in avoiding agglomeration in Pt films by using adhesion layers and combining Pt with nanostructured oxide phases.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium diboride (TiB 2 ), like borides of Zr, Cr and other transition metals, is well known for its high melting point, outstanding hardness, low specific weight, high modulus, high chemical stability, good wear resistance and so forth [1][2][3]. Due to these attractive properties, TiB 2 has extensive applications in many areas.…”
mentioning
confidence: 99%
“…23,24 The refractory nature of the borides offers a very attractive advantage as contact metallization for high-temperature device applications. While refractory borides have been investigated for contact and diffusion barrier metallizations on Si and GaAs, [25][26][27][28][29] there is very little reporting on the investigation of their suitability for Schottky contacts on SiC. Boltovets et al investigated Schottky contacts on n-type 6H-SiC using TiB 2 and found them to have very stable electrical properties under thermal stressing at 1,000°C for 2 min, where the barrier height remained around 0.7 eV and the ideality at 1.5.…”
Section: Introductionmentioning
confidence: 99%